3(-5.4n+1)+5.6n=26.5

Simple and best practice solution for 3(-5.4n+1)+5.6n=26.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-5.4n+1)+5.6n=26.5 equation:


Simplifying
3(-5.4n + 1) + 5.6n = 26.5

Reorder the terms:
3(1 + -5.4n) + 5.6n = 26.5
(1 * 3 + -5.4n * 3) + 5.6n = 26.5
(3 + -16.2n) + 5.6n = 26.5

Combine like terms: -16.2n + 5.6n = -10.6n
3 + -10.6n = 26.5

Solving
3 + -10.6n = 26.5

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -10.6n = 26.5 + -3

Combine like terms: 3 + -3 = 0
0 + -10.6n = 26.5 + -3
-10.6n = 26.5 + -3

Combine like terms: 26.5 + -3 = 23.5
-10.6n = 23.5

Divide each side by '-10.6'.
n = -2.216981132

Simplifying
n = -2.216981132

See similar equations:

| 2x+5+5x=-12 | | =84 | | 5log-7m+4=-6 | | 25+3x-x=x+4 | | 50=2(15+x) | | M-5=150 | | x^3+12x^2-5x=0 | | .35s+.6(30-s)=.45(30) | | 3y+4=8-(y+6) | | 6x-80=160 | | 34(6-7x)=4x+9 | | 0.65+0.33t=3.63t-0.67 | | 3p^2=6p | | 15z=90 | | 14+-2(3p+1)=6(4+p) | | -5x-3x+1=-14 | | -3(-4-4x)=72 | | ok= | | Sinx=.5299 | | x^2-8x+16=-x^2+20 | | 6x+8y=260 | | 16=1.6x | | 3p^2=2p | | 3(4e-7)=27 | | 2x+8y-16w= | | 3x^2+21x-4x=218 | | Sinx=.8660 | | 2(x^2-4x-2)=0 | | 1/6k+2k=65/8 | | 2x^2+4x-12=x^2+4x+24 | | 10x-3x+20=4x+53 | | 3(5.4n+1)+5.6n=26.5 |

Equations solver categories